Design Simulation Queue Cake Shop With Lamport's Bakery Algorithm - Roberth Ricki Manaha Manaha; Janeman Summah (Jurnal Info Sains : Informatika dan Sains, 2021)
Mutual exclusion is one of the mechanisms that can be used to solve concurrency problems in the operating system. In the operating system, there are resources that cannot be shared at the same time, such as printers. These kinds of resources are called critical resources. Programs that use critical resources are called entering critical regions/sections. Programmers cannot rely on the operating system to understand and enforce these limits. The mutual exclusion settlement process was submitted by several experts. One of them is Lamport with a method known as Lamport's Bakery Algorithm. The work process of Lamport's Bakery Algorithm starts from the buyer entering the store and receiving the sequence number. If there is a waiter who is idle (not being / will serve other buyers), then the buyer directly asks for service from the waiter. If not, then the buyer sits in the buyer's waiting area and waits until his turn. Shoppers who have finished being served out of the store and waiters who are idle serve the lowest numbered buyers who are waiting at the waiting place of the buyer